Pengaruh Faktor Harga, Lokasi Serta Citra Merek Terhadap Kepuasan Konsumen Membeli Perumahan di Citraland Celebes - Romansyah Sahabudin; Muhammad Irsyad; Zulfajry Al Syafaat; Nova Anggreani; Miftahul Iman (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2023)
One important component of people's welfare is owning a house. Every family now faces the pressure of meeting the main priorities, namely food and clothing or having a decent home for their own family as a result of increasingly advanced times and rapid population growth. This research aims to determine the influence of price, location and brand image on consumer satisfaction when they buy a house in Citraland Celebes Makassar. Currently, a house is not only one of the main human needs but also a determinant of social status in society, so many people are trying to have a nice house. Apart from that, a house can also be used as an investment item if it has a strategic location so that many people have more than one house in various locations as their assets in the future. The population taken for this research were people who bought houses in the Blue Aqua Citraland Cluster, which was determined using a sample of 54 (fifty four) people and the Slovin system. Questionnaires and literature collected systematically and randomly based only on research objectives were used as a serial recording technique. The research used is quantitative descriptive research with a record analysis method using multiple linear regression and validity testing.